2023
DOI: 10.1021/acs.iecr.2c04007
|View full text |Cite
|
Sign up to set email alerts
|

Scale Synthesis of Poly(butylene carbonate-co-terephthalate) and Its Depolymerization–Repolymerization Recycling Process

Abstract: Development of biodegradable aliphatic–aromatic copolyesters has been widely accepted by society as a promising strategy to solve plastic pollution. Here, a kilogram-scale aliphatic–aromatic copolyester, poly(butylene carbonate-co-terephthalate) (PBCT), has been successfully synthesized using a 5 L steel reactor. The physical–chemical properties, including composition, microstructure, thermal properties, crystal structure, rheology behavior, mechanical properties, and water barrier property, were systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure a, the water contact angle was in a narrow range of 66.6° ± 1.5° and 69.3° ± 1° with an increasing BFu molar ratio between 20 and 60%, indicating that introducing trans CC bonds into the backbone of PBF had little effect on hydrophilicity. As compared to commercial PBAT 47 and PBST 47 copolyesters, they show close values of water contact angle . Furthermore, the water contact angle of PBFFu80 was 79.0° ± 0.3°.…”
Section: Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As shown in Figure a, the water contact angle was in a narrow range of 66.6° ± 1.5° and 69.3° ± 1° with an increasing BFu molar ratio between 20 and 60%, indicating that introducing trans CC bonds into the backbone of PBF had little effect on hydrophilicity. As compared to commercial PBAT 47 and PBST 47 copolyesters, they show close values of water contact angle . Furthermore, the water contact angle of PBFFu80 was 79.0° ± 0.3°.…”
Section: Results and Discussionmentioning
confidence: 83%
“…As compared to commercial PBAT 47 and PBST 47 copolyesters, they show close values of water contact angle. 60 Furthermore, the water contact angle of PBFFu80 was 79.0°± 0.3°. The reduction of hydrophilicity was mainly due to more perfect structures of PBFu crystals.…”
Section: Hydrophilicity Hydrolysis and Enzymatic Degradation Of Pbffumentioning
confidence: 95%
“…Luo et al reported that the PBST-50, PBST-60 and PBST-70 had the same crystal structure as PBT . Wei et al prepared poly­(butylene carbonate- co -terephthalate) copolyesters, and their results also suggested that PBCT copolymers with 49.2–74.3% of molar fractions assumed the lattice of the PBT crystal . In the PBSDT copolyesters, the content of BT units was 50%, suggesting that PBT crystals were the dominant crystal.…”
Section: Resultsmentioning
confidence: 99%
“…33 Wei et al prepared poly(butylene carbonate-co-terephthalate) copolyesters, and their results also suggested that PBCT copolymers with 49.2−74.3% of molar fractions assumed the lattice of the PBT crystal. 34 In the PBSDT copolyesters, the content of BT units was 50%, suggesting that PBT crystals were the dominant crystal. The XRD patterns in Figure 2d also support this judgment.…”
Section: Thermal Properties Of Pbsdtmentioning
confidence: 99%
“…Dimethyl carbonate (DMC) is a nontoxic, sustainable, green organic synthesis intermediate produced with CO 2 as raw material. It was industrially produced by Asahi–Kasei, making DMC an ideal vehicle for preparing sustainable materials. DMC is widely used in research on the synthesis and application of polycarbonates represented by aliphatic polycarbonates (APCs) and their copolyesters. However, the weakness of heat resistance and mechanical properties of APCs make it difficult to use in further applications, which are usually improved by copolymerizing aromatic or aliphatic units and deriving a new class of polymers, polyester-polycarbonate. However, polyester-polycarbonates with fully rigid structures are difficult to prepare by traditional transesterification methods, and their glass transition temperatures are limited by the aliphatic diol. It cannot be further improved, which is much lower than that of commercial PETG, a commonly used copolyester with high transparency, tunable thermal properties, and good mechanical properties, making it difficult to be used in hot filling, cosmetics, or broader areas.…”
Section: Introductionmentioning
confidence: 99%